Impact on Outcome of Different Mechanisms, Baseline Degree and Changes of Mitral Regurgitation in Patients With Aortic Stenosis Who Underwent Transcatheter Aortic Valve Replacement - Francesco Melillo; Annamaria Tavernese; Vincenzo Rizza; Francesco Putortì; Alberto Preda; Francesco Ancona; Giacomo Ingallina; Stefano Stella; Antonio Colombo; Marco Ancona; Alaide Chieffo; Nicola Buzzatti; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Mitral regurgitation (MR) is frequent in patients with aortic stenosis (AS). Although primary MR is an established negative prognostic factor, whether different mechanisms of MR have different effects on outcome is currently unknown. The aim of this study was to evaluate the impact of the MR mechanism in patients undergoing transcatheter aortic valve replacement (TAVR). Methods and Results This is a retrospective observational study of patients who underwent TAVR for severe aortic stenosis in a high‐volume tertiary care center. Echocardiographic comprehensive MR assessment was performed at baseline and within 3 months post TAVR. The study population was divided into 4 groups according to MR mechanism: Group I: fibro‐calcific leaflet degeneration; Group II: prolapse/flail; Group III: ventricular secondary MR (functional MR); and Group IV: atrial functional MR. The study end point was a combination of death from cardiovascular cause and heart failure–related hospitalization. The study population included 427 patients (mean age 81.7±6.5 years; 71% primary MR; 62% ≥moderate MR). At 3‐year follow‐up, survival free from the composite end point significantly differs according to MR mechanism: it was higher in group IV (atrial functional MR, 96.6%) compared with group I (80.4%, P=0.002) and group II patients (60.7%, P=0.001), and group III (84.8%, P=0.037); patients with MR due to leaflet prolapse showed poorer prognosis compared with patients with functional MR (group III, P=0.023 and group IV, P=0.001) and with group I (P=0.040). Overall, severe MR after TAVR identified patients with poorer prognosis and was significantly more frequent in group II (46.4%, P=0.001). Conclusions In patients undergoing TAVR, preprocedural identification of MR mechanism and mechanism provides prognostic insights.